Evaluation of Traits’ Performance Contributing to Drought Tolerance in Sorghum - Feyissa, Tileye; Mwamahonje, Andekelile; Eleblu, John Saviour Yaw (MDPI, 2021)
Sorghum (Sorghum bicolor [L.] Moench) is an important food crop for people in semiaridAfrica. The crop is affected by post-ﬂowering drought; therefore, the study was conducted to screentraits contributing to drought tolerance using BC2F4sorghum genotypes in stressed and unstressedwater conditions in a split-plot design. Water stress (0 mm/day) was applied at post-ﬂowering toplant maturity in water-stressed treatment. The genotype SE438 produced the highest grain yield(2.65 ton ha−1) in water-stressed environment and NA316C yielded highest (3.42 ton ha−1) underwell-watered (7 mm/day) environment. There were signiﬁcant differences of most traits evaluated atp < 0.01 across environments. The mean squares of traits for genotypes by environments revealedinteractions at p < 0.05 and p < 0.01. The indices geometric mean productivity (GMP) and meanproductivity (MP) were highly correlated with yield under well-watered (YP) and water-stressedcondition (YS) and each other. The ﬁrst principal axis (PC1) explained 59.1% of the total variation.It is the best indicator of yield potential and drought tolerance of sorghum genotypes in this study.Therefore, further improvement is needed to strengthen drought tolerance and yield in sorghum.
Agronomy, Volume 11, Issue 9
Keywords: genotypes by environments; leaf rolling; panicle weight; recurrent parents; root biomass; stay green; stress intensity; Agriculture; University of Ghana; Kwadwo Ofori; Santosh Deshpande; Pangirayi Tongoona